Experimental study on flow-induced motion and energy conversion for two triangular prisms in tandem arrangement - Shao, Nan; Xu, Guobin; Wu, Zhichuan; Liu, Fang; Yan, Xiang; Wang, Xiaoqun (Frontiers in Energy Research, 2023)
Experimental tests on two tandem triangular prisms have been accomplished in synergistic flow induced motion (FIM) to collect ocean current energy (OCE) with varied spacing ratio and Reynolds number range. The typical FIM responses and energy conversion were discussed and presented. Furthermore, the effects of parameters (system stiffness, spacing ratio and load resistance) were considered to improve the energy harvesting of the system. The main findings can be summed as: (1) With varied spacing ratios between the two tandem prisms, the active power (Pharn) was up to 1.95 times than that of single triangular prism (STP). (2) In general, the harnessed OCE capacity of upstream triangular prism (UTP) was improved, while the energy harvesting of downstream triangular prism (DTP) was suppressed by the interaction of two prisms. (3) In the tests, there existed generated electricity at U=0.516 m/s and the active power, which persistently increase with flow velocity raised up, the highest active power reaches Pharn=32.24W, as well as the corresponding efficiency was ηharn=10.31%. (4) For harvesting the OCE in this paper, there exists the best energy conversion performance at L/D=5, the optimal load resistance was found as RL=11Ω.